High Performance of Ni-Al/magnetite Biochar for Methyl Orange Removal in Aqueous Solution - Palapa, Neza Rahayu; Zahara, Zaqiya Artha; Mohadi, Risfidian; Royani, Idha; Lesbani, Aldes (Science and Technology Indonesia, 2024)
Elevated concentrations of dyes in water have a significant impact on both the aquatic ecosystem and human well-being. The adsorption approach, which is cost-effective and simple to use, was chosen for color treatment. The adsorbents used in this study were Modified Layered Double Hydroxides (LDHs) and Magnetite Biochar (MBC). To prepare the Ni-Al/MBC composites, a technique called coprecipitation and hydrothermal was employed. The successful preparation of these composites was confirmed through the use of characterization tests including X-Ray Diffraction (XRD), Fourier Transform – Infra Red (FT-IR), Brunauer Emmet Teller (BET), and Vibrating Sample Magnometer (VSM). The study focused on analyzing the kinetics, isotherms, and thermodynamics of adsorption in order to anticipate the mechanism of Methyl Orange (MO) adsorption. Additionally, the regeneration process was investigated to assess the adsorbent's ability for repeated usage. The percentage of Ni-Al/MBC adsorbed during the first to fifth regeneration cycles was 86.940%, 82.545%, 70.752%, 56.244%, and 34.503% respectively. The duration of contact was 70 minutes, as determined by the Pseudo Second Order (PSO) equation, with an adsorption rate of 0.0030 g/mg.min. The Langmuir equation indicated a maximum adsorption capacity of 45.455 mg/g.